Topographical Mapping of 436 Newly Diagnosed IDH Wildtype Glioblastoma With vs. Without MGMT Promoter Methylation - Incekara, Fatih; van der Voort, Sebastian R.; Dubbink, Hendrikus J.; Atmodimedjo, Peggy N.; Nandoe Tewarie, Rishi; Lycklama, Geert; Vincent, Arnaud J. P. E.; Kros, Johan M.; Klein, Stefan; van den Bent, Martin; Smits, Marion (Frontiers in Oncology, 2020)
Introduction O6-methylguanine-methyltransferase (MGMT) promotor methylation and isocitrate dehydrogenase (IDH) mutation status are important prognostic factors for patients with glioblastoma. There are conflicting reports about a differential topographical distribution of glioblastoma with vs. without MGMT promotor methylation, possibly caused by molecular heterogeneity in glioblastoma populations. We initiated this study to re-evaluate the topographical distribution of glioblastoma with vs. without MGMT promotor methylation in light of the updated WHO 2016 classification. Methods Pre-operative T2-weighted/FLAIR and post-contrast T1-weighted MRI scans of patients aged 18 year or older with IDH wildtype glioblastoma were collected. Tumors were semi-automatically segmented and the topographical distribution between glioblastoma with vs. without MGMT promotor methylation was visualized using frequency heatmaps. Then voxel-wise differences were analyzed using permutation testing with Threshold Free Cluster Enhancement. Results Four hundred thirty-six IDH wildtype glioblastoma patients were included; 211 with and 225 without MGMT promotor methylation. Visual examination suggested that when compared with MGMT unmethylated glioblastoma, MGMT methylated glioblastoma were more frequently located near bifrontal and left occipital periventricular area and less frequently near the right occipital periventricular area. Statistical analyses, however, showed no significant difference in topographical distribution between MGMT methylated vs. MGMT unmethylated glioblastoma. Conclusions This study re-evaluated the topographical distribution of MGMT promotor methylation in 436 newly diagnosed IDH wildtype glioblastoma, which is the largest homogenous IDH wildtype glioblastoma population to date. There was no statistically significant difference in anatomical localization between MGMT methylated vs. unmethylated IDH wildtype glioblastoma.